Is corruption really bad for inequality? Evidence from Latin America - Carlyn Dobson; Antonio Rodríguez Andrés (Institute for Advanced Development Studies (INESAD), 2010)
This paper presents new evidence on the relationship between corruption and income inequality. Using a panel data methodology, we find that lower corruption is associated with higher income inequality in Latin America. This result is in contrast to other empirical studies but it makes sense in Latin America for a number of reasons. The finding of an inverse relationship between inequality and corruption suggests that institutional reform policies by themselves may be misguided.
Keywords: D73; O15; O43; 330; Inequality; Corruption; Latin America; Einkommensverteilung; Korruption; Panel; Lateinamerika